Comparative Efficacy of Combined Radiotherapy, Systemic Therapy, and Androgen Deprivation Therapy for Metastatic Hormone-Sensitive Prostate Cancer: A Network Meta-Analysis and Systematic Review - Wang, Yuhan; Gui, Huiming; Wang, Juan; Tian, Junqiang; Wang, Hanzhang; Liang, Chaozhao; Hao, Zongyao; Rodriguez, Ronald; Wang, Zhiping (Frontiers in Oncology, 2020)
Background: Recent randomized clinical trials have examined the efficacy of different combinations of systemic and local treatment approaches for metastatic hormone-sensitive prostate cancer (mHSPC). We compared the efficacy of these combined regimens in order to identify the optimal therapy for specific patient subgroups. Methods: The treatments were abiraterone (ABI), apalutamide (APA), docetaxel (DOC), enzalutamide (ENZ), and radiotherapy (RT) combined with androgen-deprivation therapy (ADT). Five electronic databases were searched up to May 7, 2020 for relevant trials. The risk of bias in the included trials was evaluated with the Cochrane tool. The hazard ratio (HR) with 95% confidence interval (CI) was determined for the included trials and indirect comparisons were performed using R software. Results: In total, 10 randomized, controlled trials with 11,194 patients were included in the meta-analysis. ADT+RT was superior to ADT monotherapy in terms of overall survival (HR=0.96, 95% CI: 0.85–1.1) and conferred a survival benefit in a subgroup of low-volume patients (HR=0.68, 95% CI: 0.54–0.87). Combined systemic treatments were significantly superior to ADT monotherapy in comparisons of survival and prostate-specific antigen response, including in the high-volume subgroup; meanwhile, in the low-volume subgroup only ADT+ENZ (HR=0.38, 95% CI 0.21–0.69) showed a significant clinical benefit. In the Gleason score<8 subgroup, all combined systemic treatments were superior to ADT monotherapy, but the results were only significant for ADT+APA (HR=0.56, 95% CI: 0.33–0.95) and ADT+DOC (HR=0.71, 95% CI: 0.54–0.92) . In the Gleason score≥8 subgroup, ADT monotherapy was inferior (albeit not significantly) to combined treatments. In a ranking of performed comparisons, ADT+ENZ was the optimal regimen, although this was nonsignificant. Combined therapies also demonstrated superiority in quality-of-life indicators such as time to skeletal events and pain progression. Conclusion: ADT+ Radiotherapy led to superior outcomes in mHSPC patients with low-volume disease. While all combined systemic regimens confer a survival advantage over ADT monotherapy, the optimal treatment approach for certain mHSPC patient subgroups remains to be determined.